Electrode, battery, and method for manufacturing electrode

A multilayer electrode structure with binders of varying swelling degrees addresses the issue of battery resistance and capacity loss at high temperatures by maintaining cohesive strength, ensuring efficient battery performance.

JP7626112B2Active Publication Date: 2025-02-04TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022139167
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-01
Publication Date
2025-02-04
Estimated Expiration
2042-09-01

AI Technical Summary

Technical Problem

Batteries, particularly lithium-ion secondary batteries, experience reduced capacity and increased resistance when stored at high temperatures due to the swelling of binders in the electrode layers, leading to decreased cohesive strength and capacity maintenance.

Method used

A multilayer electrode structure is employed, where the first layer contains a binder with a low swelling degree and the second layer contains a binder with a higher swelling degree, reducing battery resistance and improving high-temperature storage resistance by maintaining cohesive strength between the collector and electrode layer.

Benefits of technology

The multilayer electrode structure effectively suppresses the swelling of binders at high temperatures, maintaining electrode integrity and reducing battery resistance, thereby enhancing capacity maintenance during high-temperature storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626112000003
    Figure 0007626112000003
  • Figure 0007626112000004
    Figure 0007626112000004
  • Figure 0007626112000005
    Figure 0007626112000005
Patent Text Reader

Abstract

To provide an electrode capable of improving high-temperature storage resistance while reducing battery resistance.SOLUTION: A disclosed electrode is an electrode used for batteries. The electrode has a current collector and an electrode layer. The electrode layer has a first layer and a second layer from the current collector side. The first layer contains a first binder, and the second layer contains a second binder. The degree of swelling of the first binder is lower than the degree of swelling of the second binder.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to electrodes, batteries, and methods of making electrodes. [Background technology]

[0002] In recent years, with the rapid spread of electronic devices such as personal computers and mobile phones, the development of batteries to be used as power sources for these devices is progressing. In the automotive industry, the development of batteries to be used in hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs) and battery electric vehicles (BEVs) is also progressing. Among various types of batteries, lithium-ion secondary batteries have the advantage of having a high energy density.

[0003] A battery, such as a lithium-ion secondary battery, usually has a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode. The positive electrode usually has a positive electrode current collector and a positive electrode layer containing a positive electrode active material. The negative electrode usually has a negative electrode current collector and a negative electrode layer containing a negative electrode active material.

[0004] For example, Patent Document 1 discloses a multilayer electrode structure in which electrode layers each having at least a binder made of a polymeric substance and an electrode material are laminated in multiple layers on a current collector, the multilayer electrode structure being characterized in that a first electrode layer arranged in contact with the current collector and a second electrode layer arranged on the first electrode layer have different material compositions or different compounding ratios.

[0005] Patent Document 2 discloses a separator interposed between a positive electrode and a negative electrode of a lithium battery, which includes a substrate and a first layer and a second layer disposed on one surface of the substrate, and which uses different binder types for the first layer and the second layer.

[0006] Patent Document 3 discloses a method for manufacturing an electrode for a secondary battery, which includes a step of applying a first layer slurry to the surface of a current collector, a step of applying a second layer slurry onto the first layer slurry before the first layer slurry is dried, and a step of drying the first layer slurry and the second layer slurry after applying the first layer slurry and the second layer slurry to obtain a laminated structure in which the first layer and the second layer are laminated in this order on the current collector, and it is disclosed that the first layer is an active material layer and the second layer is an insulating layer that does not contain active material, and that the viscosity of the slurry differs depending on the type of binder.

[0007] Patent Document 4 discloses an electrode for a lithium ion secondary battery having a current collector and an electrode layer, the electrode layer consisting of a first electrode layer and a second electrode layer having a binder resin concentration higher than the binder resin concentration of the first electrode layer. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2001-307716 A [Patent Document 2] JP 2020-136276 A [Patent Document 3] JP 2019-096501 A [Patent Document 4] International Publication No. 2011 / 142083 Summary of the Invention [Problem to be solved by the invention]

[0009] As a result of intensive research, the present inventors have found that when a battery is stored at a high temperature (for example, 60° C.), the capacity may decrease. In addition, the battery is required to have a reduced initial resistance. The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide an electrode that can reduce the resistance of a battery and improve high-temperature storage resistance. [Means for solving the problem]

[0010] [1] An electrode for use in a battery, comprising: The electrode has a current collector and an electrode layer, The electrode layer has, from the current collector side, a first layer and a second layer, The first layer contains a first binder, The second layer contains a second binder, The electrode, wherein the swelling degree of the first binder in an electrolytic solution is lower than the swelling degree of the second binder in the electrolytic solution.

[0011] [2] The electrode according to [1], wherein a swelling degree of the first binder in the electrolytic solution is 25% or less, and a swelling degree of the second binder in the electrolytic solution is greater than 25%.

[0012] [3] The electrode according to [1] or [2], wherein the first binder and the second binder each contain a fluorine-containing binder.

[0013] [4] The electrode according to any one of [1] to [3], wherein the first binder and the second binder have the same main constituent unit.

[0014] [5] The electrode according to any one of [1] to [4], wherein the first layer and the second layer each contain an active material.

[0015] [6] the first layer and the second layer each contain an active material and a conductive material; the first layer contains a first composite in which the conductive material and the first binder are attached to a surface of the active material, The electrode according to any one of [1] to [5], wherein the second layer contains a second composite in which the conductive material and the second binder are attached to a surface of the active material.

[0016] [7] A battery having a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, A battery, wherein at least one of the positive electrode and the negative electrode is the electrode according to any one of [1] to [6].

[0017] [8] The battery according to [7], wherein the battery is a lithium ion battery.

[0018] [9] A method for producing an electrode for use in a battery, comprising the steps of: a first layer forming step of forming a first layer containing a first binder on a current collector by a dry method; a second layer forming step of forming a second layer containing a second binder by a dry method on a surface side of the first layer opposite to the current collector side to form an electrode layer including the first layer and the second layer, A method for manufacturing an electrode, wherein the swelling degree of the first binder in an electrolytic solution is lower than the swelling degree of the second binder in the electrolytic solution.

[0019]

[10] the first layer forming step includes dry-coating a first composite, in which a conductive material and the first binder are attached to a surface of an active material, onto the current collector to form the first layer; The method for manufacturing an electrode according to [9], wherein the second layer forming step forms the second layer by dry-coating a second composite having a conductive material and the second binder adhered to a surface of an active material on a side of the first layer opposite the current collector. Effect of the Invention

[0020] The electrode according to the present disclosure has the effect of reducing the resistance of the battery and improving the high-temperature storage resistance. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view illustrating an electrode according to the present disclosure. [Diagram 3] 1 is a schematic plan view illustrating an electrode according to the present disclosure. [Figure 4] FIG. 1 is a flow diagram illustrating a method for manufacturing an electrode in the present disclosure. [Diagram 5] 1 is a graph showing the relationship between the swelling degree of the binders used in Comparative Examples 1 to 3 and the reduction rate of peel strength after high-temperature storage. [Figure 6] 1 is a graph showing the relationship between peel strength and capacity retention rate after high-temperature storage for the evaluation cells of Comparative Examples 1 to 3. [Figure 7] 1 is a graph showing the relationship between the capacity retention rate after high-temperature storage and the thickness ratio of the first layer for evaluation cells of Comparative Example 1 and Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated to facilitate understanding. In addition, in this specification, when expressing an aspect in which another member is arranged relative to a certain member, the term "above" or "below" is used, unless otherwise specified, it includes both a case in which another member is arranged directly above or below a certain member so as to be in contact with the certain member, and a case in which another member is arranged above or below a certain member via another member.

[0023] A. Electrode The electrodes in the present disclosure are used in batteries. FIG. 1 is a schematic cross-sectional view illustrating a battery in the present disclosure. The battery 100 shown in FIG. 1 has a positive electrode 10, a negative electrode 20, and an electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20. The positive electrode 10 has a positive electrode current collector 1 and a positive electrode layer 2 disposed between the positive electrode current collector 1 and the electrolyte layer 30. On the other hand, the negative electrode 20 has a negative electrode current collector 11 and a negative electrode layer 12 disposed between the negative electrode current collector 11 and the electrolyte layer 30. The electrodes in the present disclosure may be a positive electrode, a negative electrode, or both a positive electrode and a negative electrode.

[0024] Fig. 2 is an explanatory diagram for explaining an electrode in the present disclosure. Fig. 2 illustrates an example in which the electrode is a positive electrode. The positive electrode 10 has a positive electrode current collector 1 and a positive electrode layer 2, and the positive electrode layer 2 has, from the positive electrode current collector 1 side, a first layer 21 and a second layer 22. The first layer 21 contains a first binder, and the second layer 22 contains a second binder, and the swelling degree of the first binder in the electrolyte is lower than the swelling degree of the second binder in the electrolyte.

[0025] The inventors of the present application have found that when a battery is stored at high temperatures (for example, 60° C.), the binder swells due to the electrolyte, which reduces the binding strength between the current collector and the electrode layer, resulting in poor electronic conductivity and a decrease in capacity. On the other hand, they have found that when a binder with a low swelling degree is used, the melt viscosity is high, which reduces the coverage of the conductive material with respect to the active material, and the battery resistance increases. They have found that an electrode that achieves both reduced battery resistance and improved high-temperature storage resistance can be obtained by forming an electrode layer into a multi-layer structure, using a first binder with a low swelling degree in the first layer disposed on the current collector, and using a second binder with a high swelling degree in the second layer disposed on the first layer, and thus completed the present invention.

[0026] 1. Electrode layer The electrode layer in the present disclosure has, from the current collector side, a first layer and a second layer. The first layer contains a first binder, and the second layer contains a second binder, and the degree of swelling of the first binder in an electrolytic solution is lower than the degree of swelling of the second binder in an electrolytic solution.

[0027] (1)First layer The first layer in the present disclosure is located between the current collector and the second layer, and contains a first binder. The swelling degree of the first binder in the electrolyte is lower than the swelling degree of the second binder in the electrolyte. By containing the first binder having a low swelling degree in the first layer, the expansion of the binder during high-temperature storage can be suppressed, and the decrease in the binding force between the current collector and the electrode layer can be prevented. As a result, the decrease in electronic conduction can be suppressed, and the decrease in capacity retention rate can be suppressed. It is preferable that the first layer is in direct contact with the current collector.

[0028] The first binder is not particularly limited as long as it has a lower swelling degree in the electrolyte than the second binder contained in the second layer. The swelling degree of the first binder is, for example, 25% or less, may be 23% or less, or may be 21% or less. In the present disclosure, the swelling degree of the binder is the weight increase rate of the binder alone when immersed in an electrolyte at 60° C. for 24 hours, and is specifically a value obtained as follows. Here, it is preferable to use the same electrolyte as that constituting the battery for measuring the swelling degree.

[0029] First, the weight of the binder processed into a sheet (weight of the binder before immersion) is measured. Next, it is immersed in an electrolyte at 60°C for 24 hours. The weight of the binder removed from the electrolyte (weight of the binder after immersion) is measured. The degree of swelling of the binder can be determined by the following formula based on the value obtained by dividing the increased weight of the binder after immersion by the weight of the binder before immersion. Swelling degree of binder (%)=((weight of binder after immersion)-(weight of binder before immersion)) / (weight of binder before immersion)×100

[0030] The first binder is usually a polymer. The first binder preferably has, for example, [-CH2-CF2-] (hereinafter, sometimes referred to as formula 1) as a constituent unit. Furthermore, the first binder preferably has a constituent unit represented by (formula 1) as the main constituent unit. "Main constituent unit" refers to the largest proportion (molar ratio) among all the constituent units constituting the binder. The proportion of the constituent unit represented by (formula 1) to all the constituent units constituting the first binder is, for example, 50 mol% or more, may be 70 mol% or more, or may be 90 mol% or more.

[0031] The first binder may have, for example, [-C2F4-] (hereinafter, sometimes referred to as formula 2) as a constituent unit. Furthermore, the first binder may have a constituent unit represented by (formula 2) as the main constituent unit. The ratio of the constituent unit represented by (formula 2) to all the constituent units constituting the first binder is, for example, 50 mol% or more, may be 70 mol% or more, or may be 90 mol% or more.

[0032] The first binder may or may not have a structural unit represented by [-CF2CF(CF3)-] (hereinafter sometimes referred to as formula 3). In the former case, the first binder may have a structural unit represented by formula 1 or formula 2 and a structural unit represented by formula 3.

[0033] Specific examples of the first binder include fluorine-containing binders (fluoride-based binders) such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene (PTFE), and fluorine rubber.

[0034] Other examples of the first binder include acrylic resin-based binders such as polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polybutyl acrylate, polyhexyl acrylate, poly2-ethylhexyl acrylate, and polydecyl acrylate; methacrylic acid resin-based binders such as polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, and poly2-ethylhexyl methacrylate; olefin resin-based binders such as polyethylene, polypropylene, and polystyrene; imide resin-based binders such as polyimide and polyamideimide; amide resin-based binders such as polyamide; polycarboxylic acid-based binders such as polyitaconic acid, polycrotonic acid, polyfumaric acid, polyangelic acid, and carboxymethyl cellulose; and rubber-based binders such as butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, and ethylene propylene rubber.

[0035] The first binder preferably has higher crystallinity and a higher melting point than the second binder. The melting point of the first binder is, for example, 155° C. or higher and 200° C. or lower, and preferably 160° C. or higher and 180° C. or lower. The melting point of the binder can be determined, for example, by differential scanning calorimetry (DSC) in accordance with the JIS K 7121 standard.

[0036] The first binder is, for example, in the form of particles. The average particle size of the particles of the first binder may be 10 nm or more and 1000 nm or less, 50 nm or more and 500 nm or less, or 100 nm or more and 300 nm or less.

[0037] The proportion of the first binder in the first layer is not particularly limited, but is, for example, 0.1% by weight or more, may be 0.5% by weight or more, or may be 1% by weight or more, while it is, for example, 15% by weight or less, may be 10% by weight or less, or may be 5% by weight or less.

[0038] The first layer usually contains an active material. The active material in the first layer may be a positive electrode active material or a negative electrode active material.

[0039] The active material in the present disclosure is, for example, a lithium transition metal composite oxide. That is, it contains Li, M1 (M1 is one or more transition metals), and O. Examples of the transition metal M1 include Ni, Co, Mn, Ti, V, Cr, Fe, Cu, and Zn. Among them, it is preferable that the active material contains at least one of Ni, Co, and Mn as the transition metal. A part of the transition metal M1 may be substituted with a metal (including a metalloid) belonging to Groups 13 to 17 of the periodic table. A typical example of a metal belonging to Groups 13 to 17 of the periodic table is Al.

[0040] Specific examples of the active material in the first layer include rock salt layered active materials such as LiCoO2, LiMnO2, LiNiO2, Li(Ni,Co,Mn)O2, and Li(Ni,Co,Al)O2; LiMn2O4, Li(Ni 0. 5Mn 1.5 )O4, Li4Ti5O 12 and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0041] The active material particles may have an average particle size of, for example, 1 μm to 50 μm, 2 μm to 30 μm, or 3 μm to 10 μm. The proportion of the active material in the first layer is not particularly limited, but may be, for example, 40% by weight or more, 60% by weight or more, or 80% by weight or more.

[0042] The first layer may further contain a conductive material. Examples of the conductive material include carbon materials. Examples of the carbon materials include particulate carbon materials such as carbon black, and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNTs), and carbon nanofibers (CNFs). Examples of the carbon black include acetylene black (AB), ketjen black (KB), and furnace black (FB).

[0043] The proportion of the conductive material in the first layer is not particularly limited, but may be, for example, 0.5% by weight or more, or 1% by weight or more, while the proportion of the conductive material is, for example, 20% by weight or less, or may be 10% by weight or less.

[0044] Moreover, the first layer usually contains an electrolyte, which will be described later.

[0045] The first layer preferably contains a first composite in which a conductive material and a first binder are attached to the surface of an active material. This is because the conductive material and the active material are in good contact with each other. In the first composite, the conductive material and the first binder are preferably attached in a dispersed state to the surface of the active material.

[0046] The first composite is usually particulate. The coverage of the binder and the conductive material in the first composite is, for example, 40% or more and 80% or less, and may be 50% or more and 75% or less. The coverage of the conductive material and the binder can be calculated, for example, by observing the composite with a scanning electron microscope (SEM) to obtain a secondary electron image and performing a binarization process.

[0047] The thickness of the first layer is, for example, 1 μm or more and 500 μm or less, and preferably 5 μm or more and 250 μm or less. It may be 15 μm or more and may be 150 μm or less.

[0048] The method for forming the first layer will be described in detail in "C. Electrode manufacturing method: 1. First layer formation step" below.

[0049] (2)Second layer The second layer is located on the side opposite to the current collector of the first layer. The second layer contains a second binder having a swelling degree higher than the swelling degree of the first binder. By containing the second binder having a high swelling degree in the second layer, the coverage of the conductive material with respect to the active material is increased, thereby reducing the battery resistance.

[0050] The second binder is not particularly limited as long as it is a binder with a higher swelling degree than the first binder contained in the first layer. The swelling degree of the second binder with respect to the electrolyte may be, for example, greater than 25%, 50% or more, or 100% or more. On the other hand, the swelling degree of the second binder with respect to the electrolyte is not particularly limited, but may be, for example, 200% or less, or 150% or less. In addition, when the swelling degree of the first binder is D1 (%) and the swelling degree of the second binder is D2 (%), the difference between D2 and D1 is, for example, 50% or more, 70% or more, or 90% or more. The method for measuring the swelling degree of the second binder with respect to the electrolyte is the same as the method for calculating the swelling degree of the first binder. The preferred embodiment of the second binder is also the same as that of the first binder described above.

[0051] The first binder and the second binder preferably have the same main constituent unit. This is because the affinity between the first layer and the second layer is improved by having the same main constituent unit. Specifically, the first binder and the second binder preferably have the above-mentioned constituent unit represented by (Formula 1) as the main constituent unit. In this case, the first binder may not have the constituent unit represented by (Formula 3), and the second binder may have the constituent unit represented by (Formula 3). For example, the first binder may be polyvinylidene fluoride (PVDF), and the second binder may be polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), which is a comonomer of vinylidene fluoride and hexafluoropropylene. PVDF-HFP has a branch structure of -CF3 in the polymer chain, and therefore has a relatively low crystallinity and a high swelling degree compared to PVDF.

[0052] When the second binder has a structural unit (HFP) represented by formula 3, the proportion of HFP contained in the second binder is, for example, 30 mol% or more, 40 mol% or more, or 50 mol% or more, based on all structural units constituting the second binder. On the other hand, the proportion of HFP contained in the second binder is, for example, 70 mol% or less, or 60 mol% or less.

[0053] The melting point of the second binder is preferably, for example, 100° C. or higher and 150° C. or lower.

[0054] The second binder is, for example, particulate. The particles of the second binder may have an average particle size of 10 nm or more and 1000 nm or less, 50 nm or more and 500 nm or less, or 100 nm or more and 300 nm or less.

[0055] The proportion of the second binder in the second layer is not particularly limited, but is, for example, 0.1% by weight or more, may be 0.5% by weight or more, or may be 1% by weight or more, while it is, for example, 15% by weight or less, may be 10% by weight or less, or may be 5% by weight or less.

[0056] The second layer usually contains an active material. The active material in the second layer may be the same as the active material in the first layer. The active material in the first layer and the active material in the second layer may have the same composition or different compositions, for example.

[0057] The second layer may further contain a conductive material. The conductive material in the second layer may be the same as the conductive material in the first layer. The conductive material in the first layer and the conductive material in the second layer may have, for example, the same composition or different compositions.

[0058] Moreover, the second layer usually contains an electrolyte, which will be described later.

[0059] The second layer preferably contains a second composite in which a conductive material and a second binder are attached to the surface of the active material. This is because the contact between the conductive material and the active material is improved. In the second composite, the conductive material and the second binder are preferably attached in a dispersed state to the surface of the active material.

[0060] The second composite is usually particulate. Since the second binder has a swelling degree higher than that of the first binder, the melt viscosity is usually lower than that of the first binder, and the coverage of the binder and the conductive material in the active material can be increased. That is, the coverage of the second binder and the conductive material in the second composite is preferably higher than the coverage of the first binder and the conductive material in the first composite. The coverage of the second binder and the conductive material in the second composite is, for example, 70% or more and less than 100%, and may be 80% or more and 95% or less. The coverage of the second composite can be calculated by the same method as the coverage of the first composite.

[0061] The thickness of the second layer is, for example, 1 μm or more and 500 μm or less, or may be 5 μm or more and 250 μm or less, or may be 15 μm or more and 150 μm or less.

[0062] The relationship between the thickness of the second layer and the thickness of the first layer is not particularly limited, and the thickness of the second layer may be greater than the thickness of the first layer, may be the same as the thickness of the first layer, or may be smaller than the thickness of the first layer. "The thickness of the second layer and the thickness of the first layer are the same" means that the absolute value of the difference between the thicknesses of the two is 3 μm or less.

[0063] The thickness of the first layer is T1 and the thickness of the second layer is T2. The ratio of T1 to the sum of T1 and T2 (T1 / (T1+T2)) (%) is, for example, 30% or more, or may be 40% or more, or 45% or more. If it is in the above range, the high temperature storage resistance is further improved. Also, the ratio (T1 / (T1+T2)) (%) is, for example, 70% or less, or may be 60% or less, or may be 55% or less. If it is in the above range, the resistance of the battery can be further reduced.

[0064] The method for forming the second layer will be described in detail in "C. Electrode manufacturing method: 2. Second layer forming step" below.

[0065] 2. Current collector The current collector in the present disclosure collects the current of the electrode layer. The electrode current collector may be a positive electrode current collector or a negative electrode current collector. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. Examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. Examples of the shape of the electrode current collector include a foil shape and a mesh shape.

[0066] 3. Electrode The electrode in the present disclosure has a current collector and an electrode layer, and the electrode layer has a first layer and a second layer from the current collector side. Fig. 3(a) is a schematic plan view illustrating an electrode in the present disclosure, and Fig. 3(b) is a cross-sectional view taken along line AA in Fig. 3(a). Fig. 3 illustrates a case where the electrode is a positive electrode. In Fig. 3, the stacking direction D of the positive electrode 10 is L In a plan view seen from the top, the area of ​​the positive electrode current collector 1 is larger than the area of ​​the first layer 21. The area of ​​the first layer 21 is also larger than the area of ​​the second layer 22.

[0067] In a plan view from the stacking direction of the electrode, the areas of the current collector, the first layer, and the second layer are S0, S1, and S2, respectively. In the present disclosure, it is preferable that S0>S1>S2. In addition, it is preferable that the first layer is formed in the approximate center of the current collector so as to overlap at least a part of the current collector in a plan view. Furthermore, it is preferable that the second layer is formed in the approximate center of the first layer so as to overlap at least a part of the first layer in a plan view. In general, since the pressure is easily released from the end of the electrode during pressing, the peel strength is weaker than that of the center, and the electrode is easily peeled off when the binder swells. Therefore, by setting the current collector, the first layer, and the second layer in the electrode to such areas and arrangements, the first layer containing a binder with a low degree of swelling is selectively arranged at the end, so that the influence during swelling can be suppressed and the electrode peeling at the end can be reduced. Therefore, the capacity retention rate is improved.

[0068] B.Battery Fig. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. The battery 100 shown in Fig. 1 has a positive electrode 10, a negative electrode 20, and an electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20. At least one of the positive electrode 10 and the negative electrode 20 corresponds to the electrode described above in "A. Electrode".

[0069] According to the present disclosure, at least one of the positive electrode and the negative electrode is the above-mentioned electrode, so that the battery resistance can be reduced and high-temperature storage resistance can be improved.

[0070] 1. Positive electrode The positive electrode has a positive electrode current collector and a positive electrode layer disposed on the electrolyte layer side of the positive electrode current collector. The positive electrode in the present disclosure preferably corresponds to the above-mentioned electrode. On the other hand, when the positive electrode in the present disclosure does not correspond to the above-mentioned electrode, the negative electrode in the present disclosure usually corresponds to the above-mentioned electrode. In this case, any conventional positive electrode can be used as the positive electrode.

[0071] 2.Negative electrode The negative electrode has a negative electrode current collector and a negative electrode layer disposed on the surface of the negative electrode current collector on the electrolyte layer side. The negative electrode in the present disclosure preferably corresponds to the above-mentioned electrode. On the other hand, when the negative electrode in the present disclosure does not correspond to the above-mentioned electrode, the positive electrode in the present disclosure usually corresponds to the above-mentioned electrode. In this case, any conventional negative electrode can be used as the negative electrode.

[0072] 3. Electrolyte layer The electrolyte layer in the present disclosure contains at least an electrolyte, such as a liquid electrolyte (electrolytic solution) or a gel electrolyte.

[0073] The electrolyte solution contains, for example, a lithium salt and a solvent. Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6; and organic lithium salts such as LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, and LiC(SO2CF3)3. Examples of the solvent include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The solvent may be one type only, or two or more types.

[0074] The gel electrolyte is usually obtained by adding a polymer to an electrolytic solution. Examples of the polymer include polyethylene oxide and polypropylene oxide. The thickness of the electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less. The electrolyte layer may have a separator.

[0075] 4.Battery The battery in the present disclosure is typically a lithium ion secondary battery. Examples of applications of the battery include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. The battery in the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.

[0076] C. Electrode manufacturing method FIG. 4 is a flow diagram illustrating a method for manufacturing an electrode in the present disclosure. The method for manufacturing an electrode shown in FIG. 4 is a method for manufacturing an electrode used in a battery, and includes a first layer forming step S1 of forming a first layer containing a first binder on a current collector by a dry method, and a second layer forming step S2 of forming a second layer containing a second binder on the surface side opposite to the current collector side of the first layer by a dry method to form an electrode layer including the first layer and the second layer, in which the swelling degree of the first binder in an electrolytic solution is lower than the swelling degree of the second binder in the electrolytic solution. In the present disclosure, the dry method refers to a method for forming a film without using a dispersion medium such as an organic solvent.

[0077] 1.First layer deposition process In the step of forming the first layer, the first composite, in which the conductive material and the first binder are attached to the surface of the active material, is preferably dry-coated onto the current collector to form the first layer.

[0078] The method for producing the first composite includes a method of compositing the active material, the first binder, and the conductive material using a composite processing device. The composite processing is preferably performed in a dry manner. For example, the composite can be performed by mixing in a mixer, a bead mill, a ball mill, a mortar, or the like, and among these, a mixer can be preferably used. In this case, the rotation speed during the composite (under load) may be, for example, 500 rpm or more and 20000 rpm or less, or 1000 rpm or more and 10000 rpm or less. The processing time may be 0.5 minutes or more and 2 hours or less, 1 minute or more and 1 hour or less, 1 minute or more and 30 minutes or less, or 1 minute or more and 20 minutes or less.

[0079] As a method for forming the first layer, for example, an electrode mixture containing the first composite is prepared, the electrode mixture is dry-coated on the surface of the current collector, and, if necessary, heated to increase the binding property or compressed to increase the density of the mixture. The composite preferably does not contain any material other than the first composite, and even if it contains a material other than the composite, it is preferable that the amount of the material is small, such as 5% by weight or less or 1% by weight or less relative to the composite. Examples of materials other than the composite include additional conductive materials and additional binders. As the additional conductive materials, additional binders, and current collectors, those exemplified in the above-mentioned description of the electrodes can be used. By performing the film formation process in a dry manner, it is possible to reduce the drying time and the amount of organic solvent used. In addition, the above-mentioned first composite has a coverage rate of the conductive material and the binder suitable for forming an electrode in a dry manner. As a dry coating method, for example, electrostatic coating using an electrostatic screen or the like is suitable.

[0080] 2.Second layer film formation process In the film-forming step of the second layer, it is preferable to form the second layer by dry-coating a second composite having a conductive material and a second binder adhered to the surface of the active material on the side opposite the current collector of the first layer.

[0081] Examples of the method for producing the second composite and the method for forming the second layer include the same methods as the above-mentioned methods for producing the first composite and the method for forming the first layer.

[0082] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0083] Comparative Example 1 (1) Composite cathode materials First, a positive electrode active material (NCM, particle size 3 to 10 μm, manufactured by Sumitomo Metal Mining Co., Ltd.), a conductive material (acetylene black (Li400, manufactured by Denka Co., Ltd.) and a binder (HSV1810 (polyvinylidene fluoride), particle size 150 nm, manufactured by Arkema) were weighed out in a ratio of positive electrode active material:conductive material:binder=97.5 / 1.5 / 1 (wt%) and placed in an MP mixer manufactured by Nippon Coke & Engineering Co., Ltd., and stirred at 10,000 rpm for 10 minutes to perform a composite treatment, thereby obtaining a composite.

[0084] (2) Film formation The obtained composite was dry-coated on a current collector foil (aluminum foil having a thickness of 12 μm) using an electrostatic screen film-forming machine (Belk Kogyo Co., Ltd.) at a voltage of 1.5 kV and a distance of 1 cm between the current collector foil and the screen.

[0085] (3) Establishment A load of 5 tons was applied for 1 minute between flat plates heated to 180°C on both sides, softening (melting) the binder and fixing the composite to the current collector foil, producing a positive electrode structure having a positive electrode current collector (current collector foil) and a positive electrode layer.

[0086] (4) Preparation of evaluation cells Next, the negative electrode active material (natural graphite) and binder (SBR and CMC) were mixed to obtain A dispersion medium was added to the mixture and stirred to obtain a negative electrode slurry. The slurry is applied onto the negative electrode current collector using a film applicator, and then heated at 80°C for 5 minutes. This resulted in a negative electrode structure having a negative electrode current collector and a negative electrode layer.

[0087] The positive electrode layer of the positive electrode structure and the negative electrode layer of the negative electrode structure were placed opposite each other with a separator interposed between them, wound, and an electrolyte was injected to obtain an evaluation cell. The electrolyte used was a mixed solvent containing EC, DMC, and EMC in a volume ratio of EC:DMC:EMC=3:4:3, with LiPF6 dissolved to a concentration of 1M.

[0088] Comparative Example 2 A positive electrode structure was produced in the same manner as in Comparative Example 1, except that the binder of the positive electrode material was changed to HSV900 (polyvinylidene fluoride, particle size 150 nm, manufactured by Arkema), and an evaluation cell was produced.

[0089] Comparative Example 3 Except for changing the binder of the positive electrode material to LBG8200 (particle size 150 nm, manufactured by Arkema), a positive electrode structure was produced and an evaluation cell was produced in the same manner as in Comparative Example 1. LBG8200 is a copolymer of PVDF and HFP (hexafluoropropylene).

[0090] Example 1 (1) Composite cathode materials First, a positive electrode active material (NCM, particle size 3 to 10 μm, manufactured by Sumitomo Metal Mining Co., Ltd.), a conductive material (acetylene black (Li400, manufactured by Denka Co., Ltd.) and a binder (HSV1810 (polyvinylidene fluoride), particle size 150 nm, manufactured by Arkema) were weighed in a ratio of positive electrode active material:conductive material:binder=97.5 / 1.5 / 1 (wt%) and placed in an MP mixer manufactured by Nippon Coke & Engineering Co., Ltd., and stirred at 10,000 rpm for 10 minutes to perform a composite treatment, thereby obtaining a first composite. Furthermore, a positive electrode active material (NCM, particle size 3 to 10 μm, manufactured by Sumitomo Metal Mining Co., Ltd.), a conductive material (acetylene black (Li400, manufactured by Denka Co., Ltd.) and a binder (LBG8200, particle size 150 nm, manufactured by Arkema) were weighed out in a ratio of positive electrode active material:conductive material:binder=97.5 / 1.5 / 1 (wt%) and charged into an MP mixer manufactured by Nippon Coke & Engineering Co., Ltd., and stirred at 10,000 rpm for 10 minutes to perform a composite treatment, thereby obtaining a second composite.

[0091] (2) Film formation The obtained first composite was dry-coated on a current collector foil (aluminum foil with a thickness of 12 μm) using an electrostatic screen film-forming machine (Belk Kogyo) to form a first layer. At this time, the voltage was 1.5 kV, and the distance between the current collector foil and the screen was 1 cm. Next, the obtained second composite was dry-coated on the first layer under the same conditions to form a second layer.

[0092] (3) Establishment A load of 5 ton was applied for 1 minute by flat plates heated to 180°C on both sides, softening (melting) the binder and fixing the composite to the current collector foil, producing a positive electrode structure having a positive electrode current collector and a positive electrode layer including a first layer and a second layer formed on the positive electrode current collector. The thickness T1 of the first layer was 100 μm, and the thickness T2 of the second layer was 100 μm. In other words, the ratio (T1 / (T1+T2)) (%) of T1 to the total of T1 and T2 was 50%.

[0093] (4) Preparation of evaluation cells An evaluation cell was produced in the same manner as in Comparative Example 1, except that the obtained positive electrode structure was used.

[0094] [Measurement of swelling degree and melting point of binder] The swelling degree and melting point of the binders used in the comparative examples and examples were measured by the above-mentioned methods. The results are shown in Table 1.

[0095] [Measurement of coverage and powder resistance] The composites obtained in the comparative example and the example were observed by SEM, binarized, and the coverage of the binder and carbon was calculated. The resistance of the composite was measured by an automatic powder resistance measuring system, low resistance version MCP-PD600. The results are shown in Table 1.

[0096] [evaluation] (IV resistance) The obtained evaluation cell was discharged for 10 seconds at currents I of 0.3C, 0.5C, and 1C, and the voltage drop ΔV over the 10 seconds was measured. The IV resistance (slope) was calculated from the relationship between the current I and ΔV. The results are shown in Table 1.

[0097] (Capacity retention rate after high temperature storage) The obtained evaluation cell was stored in a thermostatic chamber at 60° C. for 10 days. The capacity of the evaluation cell after 10 days was measured, and the capacity retention rate ((capacity after storage / initial capacity)×100%) was calculated. The results are shown in Table 2.

[0098] (Measurement of peel strength reduction rate after high temperature storage) After storing in a constant temperature bath at 60°C for 10 days, the evaluation cell was disassembled to remove the positive electrode, and the peel strength between the positive electrode current collector and the electrode layer in the positive electrode was measured using a 90° peel tester. The reduction rate of the peel strength compared to before storage was calculated using the following formula. The results are shown in Table 2. Peel strength reduction rate = ((peel strength after high temperature storage - peel strength before high temperature storage) / peel strength before high temperature storage) x 100%

[0099] FIG. 5 shows the relationship between the swelling degree of the binder used in Comparative Examples 1 to 3 and the reduction rate of peel strength. From FIG. 5, it was confirmed that when the swelling degree of the binder is high, the peel strength between the current collector and the electrode layer is reduced. Furthermore, FIG. 6 shows the relationship between the peel strength and the capacity retention rate after high-temperature storage of the evaluation cells of Comparative Examples 1 to 3. From FIG. 6, it was confirmed that there is a correlation between the peel strength and the capacity retention rate after high-temperature storage.

[0100] [Table 1]

[0101] [Table 2]

[0102] In Example 1, it was confirmed that by forming a first layer containing a first binder having a low swelling degree on a current collector, it is possible to suppress the decrease in peel strength after storage at 60°C. Furthermore, it was confirmed that, as a result, it is possible to suppress the decrease in electronic conductivity and the decrease in capacity retention rate. It was also confirmed that a low-resistance cell can be obtained by forming a second layer containing a second binder having a high swelling degree.

[0103] (Examples 2 and 3) A positive electrode structure was prepared in the same manner as in Example 1, except that the ratio (T1 / (T1+T2)) (%) of the thickness T1 of the first layer to the total thickness T1 of the first layer and the thickness T2 of the second layer was set to 10% (Example 2) and 30% (Example 3), and an evaluation cell was prepared. The capacity retention rate after high-temperature storage was measured in the same manner as above, and the results are shown in FIG. 7 together with the results of Example 1 and Comparative Example 1.

[0104] As shown in FIG. 7, it was confirmed that, compared to Example 2, Examples 1 and 3 in which T1 / (T1+T2) was 30% or more had a higher capacity retention rate after high-temperature storage. [Explanation of symbols]

[0105] 1...Positive electrode current collector 2…Positive electrode layer 10...Positive electrode 20...Negative electrode 21…1st layer 22…Second layer 11...Negative electrode current collector 12...Negative electrode layer 30...Electrolyte layer 100...battery

Claims

1. A method for producing an electrode for use in a battery, comprising the steps of: a first layer forming step of forming a first layer containing a first binder on a current collector by a dry method; a second layer forming step of forming a second layer containing a second binder by a dry method on a surface side of the first layer opposite to the current collector side to form an electrode layer including the first layer and the second layer, A method for manufacturing an electrode, wherein a degree of swelling of the first binder in an electrolytic solution is lower than a degree of swelling of the second binder in the electrolytic solution.

2. the first layer forming step includes dry-coating a first composite, in which a conductive material and the first binder are attached to a surface of an active material, on the current collector to form the first layer; 2. The method for manufacturing an electrode according to claim 1, wherein the second layer formation step forms the second layer by dry-coating a second composite having a conductive material and the second binder adhered to a surface of an active material on a surface side of the first layer opposite to the current collector.

3. A method for manufacturing an electrode as described in claim 1, wherein the swelling degree of the first binder with respect to the electrolyte is 25% or less, and the swelling degree of the second binder with respect to the electrolyte is greater than 25%.

4. The method for manufacturing an electrode as described in claim 1, wherein the first binder and the second binder each include a fluorine-containing binder.

5. A method for manufacturing an electrode as described in claim 1, wherein the first binder and the second binder have the same main constituent unit.

6. A method for manufacturing an electrode as described in claim 1, wherein the first layer and the second layer each contain an active material.

7. The first layer and the second layer each contain an active material and a conductive material, the first layer contains a first composite in which the conductive material and the first binder are attached to a surface of the active material, The method for producing an electrode according to claim 1 , wherein the second layer contains a second composite in which the conductive material and the second binder are attached to a surface of the active material.

Citation Information

Patent Citations

  • Negative plate and lithium ion battery

    CN114914393A

  • Multilayer electrode structure, battery using the same, electrical double layer capacitor, and their manufacturing methods

    JP2001307716A

  • Non-aqueous secondary battery and its production method

    JP2002110249A

  • Manufacturing method of electrode for secondary battery and manufacturing method of the secondary battery

    JP2019096501A

  • Separator and lithium battery employing the same

    JP2020136276A